Prymas Wyszyński współczesnym trenerem personalnym - Skibiński, Paweł (Społeczeństwo, 2022)
The heritage of Primate Stefan Wyszyński is very diverse. It does not only relate to political or theological areas. Many of the aspects refer to life, the problems we deal with every day. It might seem that due to Stefan Wyszyński’s teachings, it is worthwhile to perceive him as our „personal advisor”, but also as the model for everyday actions, since heroic virtues are not only about supernatural values, but also about human virtues that should be reflected in our daily existence.